2013
DOI: 10.1021/jp4088018
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Diverse Cu2O Nanoframes through Face-Selective Etching

Abstract: Two approaches have been employed to generate Cu2O nanoframes. Novel edge-truncated cubic nanoframes with empty {110} edges can be obtained directly by growing Cu2O nanocrystals in the presence of HCl etchant. After 1 h of reaction for particle growth, introduction of ethanol and sonication of the mixture effectively removes surface-adsorbed sodium dodecyl sulfate (SDS) surfactant to facilitate HCl etching. Crystal structures of the nanoframes have been examined. The entire nanoframe formation process was capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…Previously, Cu 2 O crystals have been shown to exhibit strongly facet‐dependent photocatalytic, organocatalytic, and electrical conductivity properties . Face‐selective etching and molecular adsorption on Cu 2 O particles has also been demonstrated . Recently, it was found that even the optical properties of Cu 2 O nanocrystals are facet‐dependent through spectral examination of Au–Cu 2 O core–shell nanocubes, cuboctahedra, and octahedra .…”
mentioning
confidence: 99%
“…Previously, Cu 2 O crystals have been shown to exhibit strongly facet‐dependent photocatalytic, organocatalytic, and electrical conductivity properties . Face‐selective etching and molecular adsorption on Cu 2 O particles has also been demonstrated . Recently, it was found that even the optical properties of Cu 2 O nanocrystals are facet‐dependent through spectral examination of Au–Cu 2 O core–shell nanocubes, cuboctahedra, and octahedra .…”
mentioning
confidence: 99%
“…This is due to the strong interaction between the oxygen and/or nitrogen atoms of PVP and {111} facets. In many papers, the use of sodium dodecyl sulfate (SDS) as a capping reagent has been reported [138,[143][144][145][146], however the mechanism of its selective adsorption is unclear. Its properties are supposed to be similar to those of AOT [147].…”
Section: Cu 2 Omentioning
confidence: 99%
“…Therefore, to obtain a specific form, a reducing agent is used, the most popular being: glucose [139][140][141]149], ascorbic acid (AA) [16,76,142,150] and hydroxylamine hydrochloride (NH 2 OH*HCl) [138,143,144] or hydrazine [90].…”
Section: Cu 2 Omentioning
confidence: 99%
“…So far, the synthetic strategies for hollow nanomaterials are mainly based on the application of various templates, including hard templates, so templates and self-sacricial templates. 6,[20][21][22][23][24][25][26] In the previous reports, hollow Cu 2 O nanostructures were mostly formed in the presence of surfactants, which play a so template-like role in the formation of hollow structure. In contrast, the self-sacricial template based methods are more ideal to prepare hollow nanomaterials as the templates nally convert into the products.…”
Section: Introductionmentioning
confidence: 99%